Avoidance test with earthworms (Eisenia andrei) in natural soil treated with a Bacillus thuringiensis-based biopesticide to soil quality evaluation (Research, Society and Development, 2020)
Tests using earthworms is an important preliminary screening tool in soil ecotoxicology studies. The aim was to evaluate the natural soil quality containing Bacillus thuringiensis (Bt) as an agent in a biopesticide using Eisenia andrei as bioindicator. The filter contact test was based on OECD 207 guideline and avoidance test based on ISO 17512-1, with modifications. After exposure by contact, no mortality was observed, however, excess mucus released lethargic movements and decreased touch reflexes were observed from 100 mg L-1. These results raise the question of whether sublethal effects are relevant when about the physiological effects that would harm organism and their important functions in the ecosystem. In the avoidance test, there was no response to Bt soil, suggesting that the biopesticide does not alter the soil quality or present high toxicity to E. andrei. The use of Bt biopesticides indicates to few negative effects to annelids, what suggests, at least, a viable alternative in relation to the high toxicity of chemical insecticides frequently used in agriculture.